Crafting Digital Media Audacity, Blender, Drupal, GIMP, Scribus, and Other Open Source Tools - James, Daniel; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Open source software, also known as free software, now offers a creative platform with world-class programs. Just ask the people who have completed high-quality projects or developed popular web 2.0 sites using open source desktop applications. This phenomenon is no longer underground or restricted to techies$1 (Bthere have been more than 61 million downloads of the Audacity audio editor and more than 60 million downloads of the GIMP for Windows photographic tool from SourceForge.net alone. Crafting Digital Media is your foundation course in photographic manipulation, illustration, animation, 3D modelling, publishing, recording audio and making music, DJ$1 (Bing, mixing and mastering audio CDs, video editing and web content delivery. Every technique described in the book can be achieved on GNU/Linux, but many of the applications covered run on Windows and Mac OS X as well. New to GNU/Linux and a little daunted? Don$1 (Bt worry$1 (Bthere$1 (Bs a step-by-step tutorial on Ubuntu for either temporary use or permanent installation. If you are a creative type who wants to get started with open source software or an existing GNU/Linux user looking to explore this category of programs, this is the book for you! Realize your own personal projects and creative ambitions with the tools this book will place at your fingertips.s
Working with Free Software -- Getting Started -- Tools -- Photography -- Illustration and Font Design -- Animation -- 3D Modeling -- Publishing -- Making Music -- Recording Audio -- Mixing and Mastering -- Video Editing -- Web Content.
Keywords: Computer science; Computer Science; Computer Science, general